Blood flow dynamics in microvessel bifurcations - Mohamad Tharmizi, Mohamad Ehsan (2009)
This thesis deals with the blood flow behaviour in the microvessel bifurcation using variety of blood parameters. There are two situations for the analysis which normal mircovessel and abnormal microvessel bifurcations. The objectives of this thesis are to investigate the effect of bifurcation on blood flow distributions and predict flow abnormalities due to blood properties. The thesis describes the finite volume technique to predict the abnormalities and identify the effect of the bifurcation. The structural three-dimensional solid modeling of normal and abnormal blood vessel were developed using the computer-aided drawing software. The strategy of validation of finite volume model was developed. The finite volume analysis was then performed using COSMOS Flow in Solidwork software. From the result,it is observed that bifurcation give an effect to the blood flow behavior.For normal and abnormal case, using the different pressure for same diameter of blood vessel bifurcation, the pressure result shown an increment when blood flow into the bifurcation. It is same when analyze using different velocity for same diameter, the value will decrease when it goes to the bifurcation. For analysis using different diameter of blood vessel bifurcation, the effect of bifurcation will clearly seen. Pressure and velocity will be proportional in values of analysis refer to the equation of fluid dynamics. Peak velocity of the normal and abnormal also showed different values. Normal microvessel bifurcation has a higher value of peak velocity than abnormal microvessel bifurcation. Reynolds Number also get an effect when the diameter of the blood vessel increase. Finally, the correlations obtained from this numerical result could be used to investigate the pressure and velocity distribution around the diseased segment.